Molecularly imprinted polymers and capillary electrophoresis for sensing phytoestrogens in milk - Bezdekova, Jaroslava; Vlcnovska, Marcela; Zemankova, Kristyna; Bacova, Romana; Kolackova, Martina; Lednicky, Tomas; Pribyl, Jan; Richtera, Lukas; Vanickova, Lucie; Adam, Vojtech; Vaculovicova, Marketa (Journal of dairy science, 2020)
Dairy cow feed contains, among other ingredients, soybeans, legumes, and clover, plants that are rich in phytoestrogens. Several publications have reported a positive influence of phytoestrogens on human health; however, several unfavorable effects have also been reported. In this work, a simple, selective, and eco-friendly method of phytoestrogen isolation based on the technique of noncovalent molecular imprinting was developed. Genistein was used as a template, and dopamine was chosen as a functional monomer. A layer of molecularly imprinted polymers was created in a microtitration well plate. The binding capability and selective properties of obtained molecularly imprinted polymers were investigated. The imprinted polymers exhibited higher binding affinity toward chosen phytoestrogen than did the nonimprinted polymers. A selectivity factor of 6.94 was calculated, confirming satisfactory selectivity of the polymeric layer. The applicability of the proposed sensing method was tested by isolation of genistein from a real sample of bovine milk and combined with micellar electrokinetic capillary chromatography with UV-visible detection.
Keywords: polymery; Cattle; Animals; skot; Milk; Polymers; Female; Phytoestrogens; zvířata; mléko; Electrophoresis, Capillary; Molecular Imprinting; molekulový imprinting; Genistein; fytoestrogeny; elektroforéza kapilární; ženské pohlaví; genistein